Synthesis of fluorine-containing natural gastrodin and its analogues - Lin, Y. D.; Liang, Y. D.; Liang, S. G.; Zhang, S. X.; Chi, C. S.
Reactions of 2,3,4,6-tetra-O-acetyl-n-D_glucopyranosyl bromide (2)with p-hydroxybenzaldehyde, trifluoromethyl and fluoro substi- tuted aniline and 2-amino-6-fluorobenzoic acid gave l-O-(Pformyl- pheny1)-2,3,4,6-tetra-O-acetyl-(3-D-glucopyranoside (3), l-N-(m- trifluoromethylphenylamino)-2,3.4.6-tetra-O-acetyl-~~-D-glucopyra- noside (ra), l-N-(2-carboxyl-3-fluorophenyl)-2,3,4,6-tetra-O-acetyl -Is-D-glucopyranoside (4b)and 1-N-(p-fluorophenyl)-N-(2,3,4,6-tetra -0-acetyl-F-D-glucopyranoside (4~)respectively. 1-0-(perfluoro-2- propoxypropionyl)-O-benzyl-2,3,4,6-tetra-O-acetyl-~~-D-glucopyrano- side (7)and l-O-(m-trifluoromethylphenylaminobenzylidene)-2,3,4,6 -tetra-0-acetyl-\j-D-glucopyranoside (8)were also prepared in sub- sequent reactions. Conversion of the acetyl group to the hydroxyl group yielded the corresponding deprotected product. The compounds formed have been characterized by analysis, IR, 1~ and lgF NMR and mass spectroscopy. The influence of phase-transfer catalysts on the reactions is discussed.
Keywords: GASTRODIN